O Homem da meia-noite: de troça a clube de alegoria e crítica - Carnaval de Olinda na década de 1930. - Neves, Cláudia Maria Xavier Eloy (2025)
The present work aims to show the development of the “Homem da Meia-Noite” group in 1932, which initially emerges as a “troça” and later becomes a club. Founded by a party of skilled workers, the group provided the public with great spectacles even without large budgets. With parades made up by beautiful richly decorated floats, in addition to the giant puppet and the orchestra, which paraded through the hills of the Olinda Historical Site in the 1930s. The present work aims to contribute to the historiography of the studied carnival group, which became an icon of the street carnival of Pernambuco. To understand this trajectory, newspaper articles published at the time and photographs depicting Olinda and the Momo festivities were used as sources. The sources were analyzed and worked based on bibliographic research, through the reading and analysis of books, scientific articles and dissertations. The objective was to study the society of the time in relation to its culture, customs and representations, bringing to light mainly this emblematic character of the street carnival of Pernambuco, and who consolidated himself in the historic city of Olinda, enchanting the public and contributing effectively to the success of the carnival on the slopes of Cidade Alta. The timeline of the present research starts in 1932, the foundation year of the Homem da Meia-Noite, and concludes in 1939. The result of the research will be presented in the form of a digital book aimed at the general public.